Does Measurement Matter? Examining the Impact of Outcome Measurement Variation On the Rates and Predictors of Juvenile Recidivism - Siennick, Sonja E. (American journal of criminal justice, 2024)
Concerns have been raised that cross-agency differences in the definition and measurement of juvenile recidivism may hamper the generalizability of knowledge and comparisons across jurisdictions. However, it is unclear whether measurement choices do impact the conclusions of studies of juvenile recidivism. This study examined whether the rates and the demographic, risk, and contextual predictors of juvenile recidivism varied by the operationalization of recidivism. The sample included 14,537 terms of probation of youths who completed probation in Florida between 2012 and 2016. Recidivism rates differed depending on the type of system contact and the follow-up length. Rates were comparable when adult system data were and were not included. Three-level multivariate multilevel models showed that the predictors were more strongly associated with commitment than with referral or adjudication. The directions and significance of the predictors’ effects were consistent across types of system contact, follow-up lengths, and data sources. Researchers should use varied measurement strategies, clearly describe their approach, and test for robustness across measures.